PROFILE OF PELVIC ORGAN PROLAPSE PATIENTS AT THE UROGYNECOLOGY CLINIC OF Dr. CIPTO MANGUNKUSUMO GENERAL HOSPITAL 2019–2025 - Priyatini, Tyas; Prabawati, Nirmala Gina; Syafardi, Irsat; Hayati, Nora Amalia (Majalah Kesehatan, 2026)
Pelvic organ prolapse (POP) is a common pelvic floor disorder that adversely affects women’s physical, psychological, and social well-being. Globally, approximately 30% of women may experience some degree of POP, with reported prevalence in Asian countries ranging from 3% to 50%. Limited hospital-based epidemiological data are available in Indonesia. This study aimed to describe the demographic and clinical profile of POP patients at a national tertiary referral center. A retrospective descriptive study was conducted using medical records of patients diagnosed with POP at the Urogynecology Clinic of Cipto Mangunkusumo General Hospital between 2019 and 2025. Variables analyzed included age, prolapse  severity, dominant compartment, parity, urinary disorders, type 2 diabetes mellitus, and obesity. Data were presented descriptively with 95% confidence intervals (CI). A total of 384 patients were identified, with a mean age of 57.86±12.41 years (95% CI 56.61–59.10). Most patients were aged >50 years (74.0%; 95% CI 69.6–78.4). Mild POP was observed in 52.1% and severe POP in 47.9%. Based on the compartment with the highest prolapse degree, cystocele was identified in 39.3% of cases, apical prolapse in 14.3%, and rectocele in 7.6%, while 38.8% had no single predominant compartment. A history of childbirth was documented in 83.8%, with parity 1–3 being most common (49.7%). Stress urinary incontinence (27.3%) was the predominant urinary disorder. Type 2 diabetes mellitus was found in 11.7%, and obesity in 34.0% of patients with available BMI data. In conclusion, POP patients were predominantly women aged >50 years, most with a history of childbirth. Prolapse severity was nearly evenly distributed between mild and severe cases; cystocele was the most common highest-degree compartment, followed by apical prolapse and  rectocele, with a substantial proportion of patients showing multicompartment involvement. Stress urinary incontinence was the predominant urinary disorder, and obesity and type 2 diabetes mellitus were the most common metabolic comorbidities.